(untitled) ("Conference on Universal Science Research 2023", 2024)
This article explores innovative methods for teaching English to students with speech disorders. It discusses various strategies and techniques that educators can use to facilitate effective learning and communication, highlighting the importance of personalized instruction and technology integration. The aim is to provide educators with practical insights and tools to enhance their teaching methods and support students with speech challenges in their English language acquisition journey.